1987
DOI: 10.4141/cjss87-005
|View full text |Cite
|
Sign up to set email alerts
|

The Seasonal Variation of Soil Erosion by Water in Southwestern Quebec

Abstract: Fallow plots were maintained at four sites that varied with respect to soil type and slope aspect and gradient to determine seasonal patterns of soil loss in southwestern Quebec. Equipment used to measure and record runoff included tipping-bucket flowmeters and Datapod digital recorders. Soil loss was measured on a seasonal basis from September 1983 to August 1985, to compare the percentage of annual soil loss by water that occurred during winter and summer months. Summer soil loss accounted for approximately … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
22
0

Year Published

1998
1998
2009
2009

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 0 publications
2
22
0
Order By: Relevance
“…Once again, this discrepancy may be attributed to measurement errors in soil loss because the relative error in determining sediment load increases with decreasing amount of sediment. The noncropping season soil loss under fallow of 8.1% is comparable to data reported by Wall (1981) andWall et al (1988) in southwestern Ontario, Kirby and Mehuys (1987a) in southwestern Quebec, and Black et al (1990) in southern Manitoba. They reported that for coarse-and medium-textured soils, soil loss during late-winter and earlyspring accounted for less than 10% of annual soil loss.…”
Section: Seasonal Distribution Of Runoff and Soil Losssupporting
confidence: 76%
See 4 more Smart Citations
“…Once again, this discrepancy may be attributed to measurement errors in soil loss because the relative error in determining sediment load increases with decreasing amount of sediment. The noncropping season soil loss under fallow of 8.1% is comparable to data reported by Wall (1981) andWall et al (1988) in southwestern Ontario, Kirby and Mehuys (1987a) in southwestern Quebec, and Black et al (1990) in southern Manitoba. They reported that for coarse-and medium-textured soils, soil loss during late-winter and earlyspring accounted for less than 10% of annual soil loss.…”
Section: Seasonal Distribution Of Runoff and Soil Losssupporting
confidence: 76%
“…They reported that for coarse-and medium-textured soils, soil loss during late-winter and earlyspring accounted for less than 10% of annual soil loss. A higher proportion of soil loss during snow-melt runoff was reported by Kirby and Mehuys (1987a) in fine-textured soils and van Vliet and Hall (1991) under two different rotations. By replacing 1 yr of summer fallow with barley under-seeded to red fescue in 4-yr rotations, van Vliet and Hall (1991) found that snow-melt runoff increased from 90 to 96% of the total annual runoff and soil loss increased from 39 to 80% of total soil loss.…”
Section: Seasonal Distribution Of Runoff and Soil Lossmentioning
confidence: 85%
See 3 more Smart Citations